Implementation of Model View Controller Architecture in Criticism and Suggestion Applications Using the Object Oriented Analysis and Design Method - Junadhi; Said, Shodiq Mufadhol (The Indonesian Journal of Computer Science, 2023)
STMIK Amik Riau is the first computer college in Riau, founded in 1996, and has produced thousands of graduates spread throughout Indonesia. Apart from the many achievements that have been achieved by this campus, in fact, there are still many problems that students often complain about. STMIK Amik Riau itself already has an assessment system, but it is still limited to an assessment of lecturers and services in general which are filled out once in one semester. Complaints submitted also cannot be seen and confirmed by other students so there is no benchmark that becomes a benchmark whether the complaint is worth prioritizing or not. Therefore an application system is needed that aims to provide criticism and suggestions in a transparent manner to improve the quality of the STMIK Amik Riau campus. This application will later provide a filtering feature that will display complaints based on the selected criteria using the Ascending and Descending concepts. MVC is a method used in designing applications with UML as a visual language based on the Software Development Life Cycle concept with an OOAD approach. The tools used in designing this application are Android Studio using the Flutter Framework with Dart as the main language.